(3GdNdGaI Hjf GdQaV hGdJTjYs - (3cGXe eMeO Ydj TcQs ((3HNW eDdags)
(3ChdgG (B:s
(3GdEgOGA(B: (3Edi CHhj gPg GdCeI hSjOjgG HYO GdQShd GdcQje UdhGJ Gddg Ydjge Edi CejQ GdeDefjf GdEeGe Ydj Hf CHj WGdH hHVYI GdQShd SjOI fSGA GdYdejf aGWeI HfJ eMeO(B...s
(3BNQgG (B:s
(3hdcf eG GdaGFOI ef GdGSJWGdI aj GdCSFdI hGdGSJWGdI aj GdCLhHI JLGg VjGY GdMb hGdJUeje Ydi GJHGY GdHGWd(B...s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
(3Qbej ZjQ edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds